Drift and Evolutionary Forces - Luque, Victor (THEORIA. An International Journal for Theory, History and Foundations of Science, 2016)
This article analyzes the view of evolutionary theory as a theory of forces. The analogy with Newtonian mechanics has been challenged due to the mismatch between drift and the other evolutionary forces. Genetic drift and its lack of direction has done that several authors tried to minimize or to protect its status as a force. I argue that the attempts to maintain drift as a force, in a strong manner, are not fully successful. I also show how historical and theoretical reasons explain why the Newtonian analogy arose, insofar as it is helpful in revealing the causal structure of evolutionary theory.